Performance analysis of metal hydride-based hydrogen storage system / Nur Ain Amirah Rusman - Nur Ain Amirah, Rusman (2018)
Energy is one of the basic requirements in our daily lives. The world’s energy demand is continuously increasing over the years due to the ever-increasing growth in the human population as well as economic development. At present, approximately 90% of energy demand are fulfilled by fossil fuels. With the rising demands of energy throughout the globe, it can be expected that the availability of fossil fuels is depleting at an alarming rate since fossil fuels are non-renewable sources of energy. In addition, fossil fuels are the main contributor of greenhouse gas emissions and therefore, they have a detrimental impact on human health and environment in the long term. Hence, there is a critical need to develop alternative sources of energy in replacement of fossil fuels. For that reason, hydrogen fuels have gained much interest among researchers all over the world since they are clean, non-toxic and renewable energy source. However, the greatest challenge in using hydrogen fuels lies in the development of hydrogen storage systems, especially for on-board applications. Current technologies used for hydrogen storage include highpressure compression at about 70 MPa, liquefaction at cryogenic temperature (20 K) and absorption into solid state compounds. Among the three types of hydrogen storage technologies, the storage of hydrogen in solid state compounds appears to be the most feasible solution since it is a safer and more convenient. Because of that, hydrogen stored in solid state as metal hydride has been studied for this project. In this project, a threedimensional dynamic simulation for metal hydride based hydrogen storage tank was performed using Computational Software COMSOL 5.1a Multiphysics. The software is used to simulate the charging process in the metal hydride container that is able to represent the system’s behavior. The model consists of a system of partial differential equations (PDE) describing three dimensional heat and mass transfer of hydrogen in a porous matrix and has been implemented in a finite element program that allows obtaining results on the charging variables at different studied scenarios. The model is validated against published data and later the simulation result is compared with experimental data to validate experimentally the numerical simulation. The effects of different parameters such as porosity (ε), permeability (